Bacterial diversity of soil under eucalyptus assessed by 16S rDNA sequencing analysis - da Silveira, Érico Leandro; Pereira, Rodrigo Matheus; Scaquitto, Denilson César; Pedrinho, Eliamar Aparecida Nascimbém; Val-Moraes, Silvana Pómpeia; Wickert, Ester; Carareto-Alves, Lúcia Maria; de Macedo Lemos, Eliana Gertrudes (Pesquisa Agropecuaria Brasileira, 2006)
Studies on the impact of Eucalyptus spp. on Brazilian soils have focused on soil chemical properties and isolating interesting microbial organisms. Few studies have focused on microbial diversity and ecology in Brazil due to limited coverage of traditional cultivation and isolation methods. Molecular microbial ecology methods based on PCR amplified 16S rDNA have enriched the knowledge of soils microbial biodiversity. The objective of this work was to compare and estimate the bacterial diversity of sympatric communities within soils from two areas, a native forest (NFA) and an eucalyptus arboretum (EAA). PCR primers, whose target soil metagenomic 16S rDNA were used to amplify soil DNA, were cloned using pGEM-T and sequenced to determine bacterial diversity. From the NFA soil 134 clones were analyzed, while 116 clones were analyzed from the EAA soil samples. The sequences were compared with those online at the GenBank. Phylogenetic analyses revealed differences between the soil types and high diversity in both communities. Soil from the Eucalyptus spp. arboretum was found to have a greater bacterial diversity than the soil investigated from the native forest area.